Understanding of Iban Women Political Participation through Analysing the Decision-Making Process in Iban Society - Lucy, Sebli; Stanley Bye, Kadam-Kiai (UNIMAS Publisher, 2022)
An individual is said to have become involved in politics if he or she participated in activities such as voting, campaigning, soliciting for votes, giving political speeches to influence the actions or the decisions of the other persons, becoming a member of a political organisation, distributing party fliers, carrying banners, or supporting a political party. A person’s involvement in politics may be classified as active involvement or passive involvement. The highest level of a political participation is when a person puts himself or herself up to be chosen as the people’s representative in a competitive election. To date no Iban women have ever been elected to the country’s House of Representatives. This is not to say that their involvement in ‘low politics’ is any better either. Niggling issues such as the customary practices, the longhouse systems, the political socialisation, the decision-making processes, and the notion of manliness may still be the decisive factors in how and why the Iban select or determine their leaders. This paper is an attempt to understand how and why the involvement of Iban women in politics is still at an infancy stage, as well as exploring the challenges that hinder its progress and development. Keywords: Decision making, community leader, longhouse tradition, participation, socialisation